Psychiatric disorders in Chinese immigrants during the 19th century. First part: Chinese immigrants in Lima Cercado mental hospital 1879-1902 - Li Ning Anticona, José Luis (2016)
A retrospective study was made in order to determine a psychiatric statistical profile of the hospitalized Chinese immigrants (‘coolies’) who came to Peru in the XIX century as indentured labourers after the abolition of slavery. In the archives of the Manicomio del Cercado in Lima, guarded in the Hospital Victor Larco Herrera; 58 hospitalized coolies were registered between 1859 and 1917, all of them male, mainly single and elder than 40 years old. The most frequent diagnosis (57%) was ‘toxic psychosis’, 47% associated to opium and 10% to alcohol and coca leaves consume. The rest of the diagnosis could be equivalent to schizophrenia or dementia and bipolar disorders and fewer to paranoia and epileptic psychosis. Only one patient (1.7%) was diagnosed as ‘toxic psychosis’ associated to syphilis: general paresis of the insane, the psychiatric form of neurosyphilis, whose frequency was even ten times more in other countries.